Farelo de canola em dietas de frangos de corte - Moraes, Priscila de Oliveira (2014)
This study aimed to evaluate the replacement of soybean meal by canola meal in diets of broilers on the performance, bone strength, intestinal morphology, meat quality and economic analysis. Three hundred broil ers of Cobb were housed with a day old, up to 42 days. The broilers were randomly distributed in a completely randomized design with five levels of replacement of soybean meal by canola meal (T1 - 0%, T2 - 25%, T3 - 50%, T4 - 75% e T5 100%) and six replicates with ten broilers each. The basal diets were formulated based on corn and soybean meal, meeting the nutritional requirements of broilers. To evaluate the effect of inclusion levels of canola except in sensory analysis polynomial regression analysis w as used. Sensory analysis was applied to analysis of variance and means were compared by Tukey test. The variables of weight gain and feed conversion obtained a decreasing linear response in the first week of bird life with increasing levels of replacement of soybean meal by canola meal. After 21 days of age, the chickens had no significant difference for the weekly weight gain. The relative weights of liver and heart showed a linear correlation with the increase in the canola meal diet. With respect to biometry, only the length of the jejunum at 21 days showed a linear correlation with the increase in the canola meal diet. There was a significant effect of replacing soybean meal by canola meal on bone strength only at 14 days of age, showing a quadratic response to the increasing level of 28.64 % and decreasing replacement as increased canola meal in the diet. At 35 days the calcium content increased significantly with the increase of rapeseed meal in the diet, this same age the ash content was significant, showing a quadratic response, decreasing to the level of 64.92 % replacement of soybean meal by canola meal and increasing thereafter. The villus height in the duodenum and jejunum showed a decreasing linear response, unlike the ileum, which showed a linear response increasing the protein content of chicken leg showed a quadratic response to the increasing level of 40.21 % and decreasing thereafter as increased content of canola diet. The lipid content in both the leg and the breast of broilers also showed a quadratic response decreasing, respectively, to levels of 26.83 % and 30.75% replacement of soybean meal by canola meal, increasing thereafter. Differences in sensory evaluation for color , odor, taste and hardness were found. With respect to economic ana lysis in the growth phase was achieved higher gross income to the replacemen t level of 25 %. In conclusion, canola meal can replace soybean meal to the level of 25 % growth in the diet of broiler chickens, however further studies are needed.